Potentiometric Sensor for Furosemide Determination in Pharmaceuticals, Urine, Blood Serum and Bovine Milk - Santini, Alberto O. [UNESP]; Pezza, Helena Redigolo [UNESP]; Sequinel, Rodrigo [UNESP]; Rufino, Jose L. [UNESP]; Pezza, Leonardo [UNESP] (Soc Brasileira Quimica, 2009)
The construction, evaluation and analytical application of a potentiometric sensor, namely, Pt vertical bar Hg vertical bar Hg(2)(Fur)(2)vertical bar Graphite, where Fur stands for 4-chloro-N-furfuryl-5-sulphamoyl-anthranilate ion, are described. This electrode has a linear dynamic range between 5.0 x 10(-7)-1.0 x 10(-2) mol L(-1) with a near-Nernstian slope of (-58.4 +/- 0.9) mV decade(-1) and a detection limit of 3.8 x 10(-7) mol L(-1). The potentiometric response is independent of the pH of the solution in the pH range 7.0-9.0. The electrode shows easy construction, low-cost, fast response time (within 10-20 s) and can be used for a period of 6 months without significant change in its performance characteristics. The proposed sensor displayed good selectivities over a variety of other anions (carboxylates and inorganic anions). Application of this potentiometric sensor for the furosemide determination in pharmaceuticals, urine, blood serum and commercial milk samples is reported.
Keywords: 4-cloro-N-furfuryl-5-sulphamoylanthranilate-sensitive electrode; potentiometry; pharmaceuticals; urine; human blood serum; bovine milk